Peningkatan Pendapatan Ibu-ibu Rumah Tangga di Ngebel Melalui Kerajinan Bunga Pinus - Muhammad Hanif; Sri Wahyuni; Muryanto Muryanto (Communio: Jurnal Pengabdian Kepada Masyarakat, 2023)
Ngebel Village, Ponorogo has a very large pine forest area. Communities that are still dependent on forest products experience economic instability. In addition, work in the forest is work done by men or the head of the household so that housewives who do not have a permanent job depend on the head of the household for their needs. Community empowerment uses the community development practice method, which aims to transfer knowledge and technology to housewives to be creative and innovative in utilizing forest potential, one of which is the potential of pine cones. Through crafts that are made, this can provide additional income for housewives. So that it can help the household economy.